2016
DOI: 10.1111/eci.12634
|View full text |Cite
|
Sign up to set email alerts
|

Casein glycomacropeptide for active distal ulcerative colitis: a randomized pilot study

Abstract: The addition of CGMP as a nutritional therapy to standard treatment was safe and accepted by patients with active distal UC. The disease-modifying effect of CGMP was similar to that of the mesalamine dose escalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…This highly glycosylated 64-amino acid peptide presents an average molecular weight of 7.5 kDa [ 22 ]. It is considered safe for human use and is not immunogenic regardless of the administration route [ 23 , 24 ]. GMP is free from phenylalanine residues, which allows it to be used as a protein-based ingredient in the formulation of food products for the nutrition of phenylketonuria patients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This highly glycosylated 64-amino acid peptide presents an average molecular weight of 7.5 kDa [ 22 ]. It is considered safe for human use and is not immunogenic regardless of the administration route [ 23 , 24 ]. GMP is free from phenylalanine residues, which allows it to be used as a protein-based ingredient in the formulation of food products for the nutrition of phenylketonuria patients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study indicates that GMP has potential as a bioactive ingredient which could assist in improving the gastrointestinal health of individuals. Indeed, recently GMP has shown promise as a nutritional therapy in patients with active distal ulcerative colitis [ 68 ]. Moreover, methods for producing GMP based on its glycosylation and the effect of its glycosylation on the peptide’s techno-functional properties have been documented [ 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study conducted in patients with ulcerative colitis, observed anti-inflammatory clinical effects of CGMP after four weeks. (40) Studies of dietary-induced CRP changes reported CRP decreases after two to three weeks. (41,42) Regarding the impact of dietary intervention on microbiota composition, studies found changes after five days to four Accepted manuscript amino acids, arginine, cysteine, and histidine.…”
Section: Methodsmentioning
confidence: 99%